A Habermasian-based critical discourse analysis of the ICT strategies of the Centre for e-Innovation, Provincial Government of the Western Cape - Vosloo, Steve (Faculty Commerce: IT, 2024)
There is much political discourse concerning the role of information and communication technologies (ICTs) in supporting the achievement of development goals. Given the increasing prevalence and importance of ICTs in society, the Centre for e-Innovation (Cel), Provincial Government of the Western Cape, South Africa, has prepared five strategic documents outlining how to utilise ICTs for development and create an information society in the province. Amidst the discourse about ICT for development there is, however, a recurrent theme of technological determinism, which is shown to be a cause of the high failure rate of ICT for development projects. Based on the approach of Cukier, Middleton & Bauer (2003) and Cukier, Bauer and Middleton (2004) to operationalising Habermas' validity claims to assess communicative rationality, I conducted a critical discourse analysis (CDA) of the five Cel strategic documents to determine whether or not these are distorted, e.g. through claims of technological determinism. The study found a large number of distortions in the discourse. Suggestions are provided for how to create less distorted strategies, which more closely resemble Habermas' ideal speech situation.